ANALISIS KEMAMPUAN GURU DALAM PELAKSANAAN PEMBELAJARAN DIFERENSIL PADA MATA PELAJARAN IPAS DI KELAS IV SDN 132 BULUJAMPI KABUPATEN SINJAI - Sudarto, Sudarto; Satriani, Satriani; Syahrul Amrullah Fattah (Jurnal Cakrawala Ilmiah, 2025)
This research is motivated by the importance of the differentiated learning in accommodating the diverse learning needs of the students, especially in IPAS subjects in the 4th Grade of elementary school. However, based on the teacher's view in implementing it, he or she still faces various obstacles, especially related to the teacher's ability ino design and implement the differentiated learning comprehensively. This type of research is a descriptive qualitative research that aims to describe the teacher's ability in implementing the differentiated learning. The data were collected through the interviews, observations, and questionnaires and data analyzed using: data reduction, data presentation, and drawing conclusions based on the Miles and Huberman techniques. The research was conducted at SDN 132 Bulujampi, Sinjai Regency with the 4th Grade teacher as the subject. The supporting instruments in this study were interview guidelines, observation sheets, and questionnaire sheets. Results and conclusions: the ability of the 4th Grade teacher of SDN 132 Bulujampi in implementing the differentiated learning in IPAS subjects are (1) the ability of the teacher in terms of identifying the student needs: teacher is able to understand the student diversity in order to design learning, (2) the ability of the teacher in terms of learning procedures: teacher is able to use various learning procedures that are varied and in accordance with the student needs, (3) the ability of the teacher in terms of content differentiation: teacher is able to provide the relevant materials and in accordance with the needs and learning styles of the students, (4) the ability of the teacher in terms of process differentiation: teacher is able to provide guidance to all the students in following learning well, (5) the ability of teacher in terms of product/task differentiation: teacher is able to provide the differentiated tasks and (6) in terms of providing the feedback and assessment, teacher is able to provide the feedback and assessment that is in accordance with the student development